Development of a Taxonomy of Policy Interventions for Integrating Nurse Practitioners into Health Systems - Joshua Porat-Dahlerbruch; Shoshana Ratz; Moriah Ellen (Kerman University of Medical Sciences, 2023)
Background  Nurse practitioners (NPs)-nurses with advanced training who can provide and prescribe care-are increasingly prevalent internationally. The growth of NPs can be attributed to physician shortages, growing demand for health services, and the professionalization of nursing. Ensuring efficacious integration of NPs into the health system is critical for maximizing their impact on patient and system outcomes. Nonetheless, there is a dearth of information on practical policy interventions facilitating the successful integration of NPs. Effective policy interventions should capture the perspectives of actors at all levels of the health system-ie, national and organizational levels. This study aimed to delineate a taxonomy of policy interventions for integrating NPs into health systems. This paper presents a taxonomy developed among gerontology NPs in Israel. Methods  This qualitative descriptive study used multiple perspective, one-to-one interviews with four professional groups-national policy-makers, organizational administrators, NPs, and physicians. Data were analyzed using deductive content analysis. Analysis accounted for diverging and converging patterns between professional groups.  Results: There were 58 participants across the four professional groups. The national-level domain interventions include marketing, workforce development, professional licensure and regulation, financial incentives, stakeholder cooperation, education and training programs, and national-level research. Organizational domain interventions included organizational guidelines, infrastructure development and resource allocation, interprofessional leadership engagement, and organizational messaging. Unit- and care-team domain interventions included interprofessional experience and exposure, team communication, and mentorship. Conclusion  The taxonomy's trichotomy of three health system level domains describes the relationship between national and organizational policy interventions. Adopting these interventions may result in an improved response to provider shortages. Policies insufficiently addressing role clarity and workforce retention resulted in poor integration and a failure to efficaciously combat workforce shortages. Future work will expand the focus of this preliminary taxonomy by further development and testing with international participants.